A novel receive-only liquid nitrogen (LN2)-cooled RF coil for high-resolution in vivo imaging on a 3-Tesla whole-body scanner - Hu, Bobo; Varma, Gopal; Randell, Chris; Keevil, Stephen F.; Schaeffter, Tobias; Glover, Paul (IEEE, 2012)
The design and operation of a receive-only liquid nitrogen (LN2)-cooled coil and cryostat suitable for medical imaging on a 3-T whole-body magnetic resonance scanner is presented. The coil size, optimized for murine imaging, was determined by using electromagnetic (EM) simulations. This process is therefore easier and more cost effective than building a range of coils. A nonmagnetic cryostat suitable for small-animal imaging was developed having good vacuum and cryogenic temperature performance. The LN2-cooled probe had an active detuning circuit allowing the use with the scanner's built-in body coil. External tuning and matching was adopted to allow for changes to the coil due to temperature and loading. The performance of the probe was evaluated by comparison of signal-to-noise ratio (SNR) with the same radio-frequency RF) coil operating at room temperature (RT). The performance of the RF coil at RT was also benchmarked against a commercial surface coil with a similar dimension to ensure a fair SNR comparison. The cryogenic coil achieved a 1.6- to twofold SNR gain for several different medical imaging applications: For mouse-brain imaging, a 100-mu m resolution was achieved in an imaging time of 3.5 min with an SNR of 25-40, revealing fine anatomical details unseen at lower resolutions for the same time. For heavier loading conditions, such as imaging of the hind legs and liver, the SNR enhancement was slightly reduced to 1.6-fold. The observed SNR was in good agreement with the expected SNR gain correlated with the loaded-quality factor of RF coils from the EM simulations. With the aid of this end-user-friendly and economically attractive cryogenic RF coil, the enhanced SNR available can be used to improve resolution or reduce the duration of individual scans in a number of biomedical applications.